2011
DOI: 10.1002/anie.201006331
|View full text |Cite
|
Sign up to set email alerts
|

LiZnSO4F Made in an Ionic Liquid: A Ceramic Electrolyte Composite for Solid‐State Lithium Batteries

Abstract: The search for good solid electrolytes constitutes a major goal towards the development of safer lithium batteries. A few candidates do exist, but they suffer either from narrow electrochemical window stability or too low ionic conductivity. Herein we report the ionic-liquid-assisted synthesis of a novel LiZnSO 4 F fluorosulfate phase having a sillimanite LiTiOPO 4 -type structure, which on simply pressed samples shows a room-temperature ionic conductivity of 10 À5 -10 À7 S cm À1 together with a 0-5 V electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 23 publications
1
51
1
2
Order By: Relevance
“…A comparison between the high resolution 1 H (e) and 19 F (f) NMR spectra of LiZnSO 4 F-IL and LiZnSO 4 F-C clearly shows the presence of EMI and TFSI molecules in the samples (e, f), together with some residual water, either in LiZnSO 4 F-C ( ≈ 6.5 ppm) or in the grafted ionic liquid layer for LiZnSO 4 F-IL ( ≈ 1.8 ppm) (e). Some LiF is also detected by 19 F NMR (b, f) lower ionic conductivity for the sillimanite LiZnSO 4 F than the tavorite LiMSO 4 F phases, the opposite of what we observed [7,8,11,16]. So, solely from structural perspective, the high value of conductivity is difficult to explain.…”
Section: Resultscontrasting
confidence: 44%
See 2 more Smart Citations
“…A comparison between the high resolution 1 H (e) and 19 F (f) NMR spectra of LiZnSO 4 F-IL and LiZnSO 4 F-C clearly shows the presence of EMI and TFSI molecules in the samples (e, f), together with some residual water, either in LiZnSO 4 F-C ( ≈ 6.5 ppm) or in the grafted ionic liquid layer for LiZnSO 4 F-IL ( ≈ 1.8 ppm) (e). Some LiF is also detected by 19 F NMR (b, f) lower ionic conductivity for the sillimanite LiZnSO 4 F than the tavorite LiMSO 4 F phases, the opposite of what we observed [7,8,11,16]. So, solely from structural perspective, the high value of conductivity is difficult to explain.…”
Section: Resultscontrasting
confidence: 44%
“…However, the high conductivity value in the case of LiZnSO 4 F-IL was a surprise, which can arise either due to structure or surface modification. LiZnSO 4 F stabilizes into a different structure (orthorhombic, s.g. Pnma [11]) than other LiMSO 4 F compounds (triclinic, s.g. P-1), which leads to a one-dimensional diffusion of Li for LiZnSO 4 F as compared to a three-dimensional one for LiMSO 4 F phases. It leads to the expectation of having a /cooling (a, c), seemingly indicating no change in the bulk LiZnSO 4 F lithium mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyanionic systems form a treasure box for chemist to unravel new materials with rich structural diversity and formidable electrochemical properties. The role of 3d transition metals is striking in forming diversified structures and polymorphs depending upon different synthesis conditions [12][13][14]. Add to this, the polyanionic frameworks have been shown to deliver the highest redox potential for Fe 3+ /Fe 2+ (ca.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, this type of materials becomes a candidate of the new-generation cathode material for Li + batteries. [1][2][3] Recently, it was reported that LiZnSO 4 F with a 3D structure framework was adequate for a ceramic electrolyte, 4 and the ferrous homologue LiFeSO 4 F and NaFeSO 4 F were reported as intriguing electrode materials 2,5 with obvious advantages such as low toxicity and high Li + diffusivity. The analogues based on PO 4 F 4− polyanion (e.g.…”
Section: Introductionmentioning
confidence: 99%